Percutaneous kidney biopsy: eight years-experience. - Castro, Rui (2004)
Renal biopsy is a fundamental tool in the diagnosis and prognostic of multiple nephrological and systemic pathologies. At our institution the first patient submitted to this technique, at 1994, showed Berger disease. Until 2002 we have performed 91 renal biopsies (57 men and 34 women) with the following annual distribution: 1994 (n=3), 1995 (n=3), 1996 (n=3), 1997 (n=15), 1998 (n=5), 1999 (n=23), 2000 (n=13) and 2001 (n=26). Ultrasound guidance was always used and in most of cases the technique was performed with Vim-Silverman (14G) needle. BARD automatic system was employed in only five patients. The clinical diagnosis that lead to renal biopsy were: nephrotic syndrome (n=27), asyntomatic urinary abnormalities (n=25), acute or rapidly progressive renal failure (n=18), chronic renal failure (n=15), hypertension (n=4) and acute nephritis (n=2). The efficacy for optic histological diagnosis was 92.3% (84/91). However, if we include seven cases of presumed IgA nephropathy that don't included fragment for immunofluorescence (IF) analysis the efficacy declined to 84.6% (77/91). The mean number of glomeruli per fragment was 18.3 -/+ 14.2 [0-80]. Histological diagnosis were the following: Berger disease (n=24), idiopathic nephrotic syndrome (n=18), lupus nephritis (n=8), mesangial proliferative glomerulonephritis without glomeruli in the IF fragment (n=6), without glomeruli (n=6), secondary nephrotic syndrome (n=4), tubulointerstitial nephritis or acute tubular necrosis (n=4), diabetic nephropathy (n=3), myeloma kidney (n=3), pauci-imune and crescentic glomerulonephritis (n=3), hypertensive nephropathy (n=2), IgM mesangial proliferative glomerulonephritis (n=2) and various (n=8). Gross hematuria appeared in 9 patients (9.9%). Only in three of these patients it was showed, by ecography, the existence of kidney haematoma. Bleeding throughout the mandrill in four cases, leaded to transfusion in only three patients. We have registered one accidental spleen puncture. Nephrectomy for incontrollable bleeding was never needed. Higher glomerulosclerosis (30% vs 8%; p